Clinical activity and tolerability of enzalutamide (MDV3100) in patients with metastatic, castration‐resistant prostate cancer who progress after docetaxel and abiraterone treatment. Issue 7 (30th December 2013) - Badrising, Sushil; van der Noort, Vincent; van Oort, Inge M.; van den Berg, H. Pieter; Los, Maartje; Hamberg, Paul; Coenen, Jules L.; van den Eertwegh, Alfons J. M.; de Jong, Igle J.; Kerver, Emile D.; van Tinteren, Harm; Bergman, Andries M.
<x xml:space="preserve">Abstract</x> BACKGROUND Enzalutamide (Enz) and abiraterone acetate (AA) are hormone treatments that have a proven survival advantage in patients with metastatic, castration‐resistant prostate cancer who previously received docetaxel (Doc). Recently, limited activity of AA after Enz and of Enz after AA was demonstrated in small cohort studies. Here, the authors present the activity and tolerability of Enz in patients who previously received AA and Doc in the largest cohort to date. METHODS The efficacy and tolerability of Enz were investigated in men with progressive, metastatic, castrate‐resistant prostate cancer who previously received Doc and AA. Toxicity, progression‐free survival, time to prostate‐specific antigen (PSA) progression, and overall survival were retrospectively evaluated. RESULTS Sixty‐one patients were included in the analysis. The median age was 69 years (interquartile range [IQR], 64‐74 years), 57 patients (93%) had an Eastern Cooperative Oncology Group performance status from 0 to 2, 48 patients (79%) had bone metastases, 33 patients (54%) had lymph node metastases, and 13 patients (21%) had visceral metastases. The median duration of Enz treatment was 14.9 weeks (IQR, 11.1‐20.0 weeks), and 13 patients (21%) had a maximum PSA decline ≥50%. The median progression‐free survival was 12.0 weeks (95% confidence interval [CI], 11.1‐16.0 weeks), the median time to PSA progression was 17.4 weeks (95% CI, >16.0 weeks), and the median overall survival was 31.6 weeks (95% CI, >28.7 weeks). Enz was well tolerated, and fatigue and musculoskeletal pain were the most frequent grade ≥2 adverse events. The PSA response to Doc and AA did not predict the PSA response to Enz. CONCLUSIONS Enz has modest clinical activity in patients with metastatic, castrate‐resistant prostate cancer who previously received Doc and AA. PSA response to Doc and AA does not predict for PSA response to ENz. Cancer 2014;120:968–975. © 2013 American Cancer Society.